Opening the door – first insights into the music therapy room's design. Issue 5 (20th October 2017) - Goditsch, M. J.; Storz, D.; Stegemann, T.
ABSTRACT: The basis of the present paper is formed by the assumption that the physical environment of music therapy influences the music therapy protagonists and the therapy process. The first part of this research consists of an explorative theoretical study, in which pertinent disciplines are searched for findings regarding the relation between people and space. The revealed interdisciplinary findings offer a multi-perspective on the present topic and serve as basis to establish music therapy room's atmospheric parameters . In the second part, a systematic search of music therapy publications was carried out with focus on considerations and recommendations regarding the music therapy room and its atmospheric parameters. A mutual interaction between people and space can be acknowledged. The music therapy room's atmospheric parameters include the room's characteristics, lighting, temperature, odours, colours and the room's design, arrangement and equipment. The extracted statements in the second part point out some important topics for music therapy, like sound-insulation, the seating arrangement or the therapy room's possible function as a safe place. It becomes obvious that the influence of the music therapy's environment is taken as self-evident in music therapy literature. However, the present topic represents an almost blank field in music therapy research and publication.